Evaluation of Swallowing Disorder in Ischemic Stroke Patients By Flexible Endoscopic - Nur Indah Lestari Lestari; Widjajalaksmi Kusumaningsih; Salim Harris; Susyana Tamin; Retno Asti Werdhani (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Dysphagia is one of the complications of stroke and closely associated with increasing of aspiration pneumonia. Evaluation of dysphagia was necessary to prevent pneumonia due to aspiration has effectively done by fiberoptic endoscopic evaluation of swallowing (FEES).Methods: The study was a cross sectional study with convenience sampling. The subjects were stroke outpatients from July to December 2018. The FEES was conducted to assess the swallowing dysfunction and the data were collected.Results: There was six post ischemic stroke subjects, mean age (SD) was 55.17 (9.13) years and 4 subjects were male. All subjects had standing secretion in pre-swallowing assessment. 3 subjects used nasogastric tube (NGT) to fulfill the intake safely. In swallowing assessment, all subjects had residue at vallecula and/or pyriformis sinus. 2 subjects had penetration only and 4 subjects had penetration with aspiration. There was inadequate cough reflex in 2 subjects.Conclusion: Standing secretion and residue became the most dominant findings in post ischemic stroke patients, which a risk to have Aspiration.Keywords: Swallowing Disorder, Stroke, Flexible Endoscopic Evaluation of Swallowing (FEES)